Radiolarian Research in Some Mesozoic Provinces in Indonesia - Munasri Munasri (Berita Sedimentologi, 2001)
The single-celled radiolarians average between 20-200 mm in diameter. These planktonic animals range from Cambrian to Holocene. The name Radiolaria was first proposed by Muller (1858) for marine Sarcodina with radial symmetry to distinguish them from foraminifera. Ehrenberg (1838) proposed the name of Polysystina for fossil skeletons consisting of soild opaline processes. This group includes the two taxa Spumellaria (spherical) and Nassellaria (bell shaped).Although Radiolaria has been known since 19th century, but their fossils were only comprehensively treated for stratigraphic purpose within the last three decades. The new way of extraction of radiolarian-bearing rocks by using hydrofluoric acid solution; and the use of scanning electron microscope have also rapidly enhanced the development of radiolarian research.Recent studies of Radiolaria mostly emphasize their value to biostratigraphic correlation of marine sediments, as almost any initial report of the Deep-Sea Drilling Project has demonstrated.Radiolarians are particularly useful where other microfossils have suffered dissolution. They have also been used to indicate paleogeographic and tectonic change in ocean basin. For examples, radiolarians stratigraphy gave early support to the hypothesis of sea-floor spreading (Riedel, 1967); and paleogeographically distinct low- and high-paleolatitude faunas were described by Baumgartner (1993).